Christmas in the castle library [large type] - Swindell, Ann (In the castle library, 2024)
"Ellie Sawyer has always felt more comfortable with books than people, which explains why she's now a PhD history student, neck-deep in research, and trying to complete her doctoral dissertation in time to graduate. But the final books she needs are half a world away, in the tiny European country of Lethersby -- and the only time she can access the highly secretive Royal Castle Library is over the Christmas holidays. Ellie is determined to get to the bottom of the mystery that has eluded Lethersby scholars for over one hundred years by figuring out what happened to their long-lost queen, a young royal who disappeared into the night shortly after the outbreak of WWI. And with the help of Mark, the handsome castle staff member who shares her love of history, she just might be able to unravel the queen's story. But Mark is keeping his own secret from her, and what they discover together could change everything for Ellie -- and the entire kingdom."--